Znf76 is associated with development of the eyes, midbrain, MHB, and hindbrain in zebrafish embryos - Jangham Jung; S. Udhaya Kumar; Issac Choi; Tea-Lin Huh; Myungchull Rhee (Animal Cells and Systems, 2019)
ZNF76 is a transcriptional repressor that targets the TATA-binding protein (TBP) and plays an essential role during brain development; however, its function during embryogenesis remains unclear. Here, we report the expression pattern and potential functions of znf76 in zebrafish embryos. Maternal transcripts of znf76 were detected at low levels in embryos at the 1-cell stage, with zygotic transcripts appearing at the sphere stage. At the bud stage, the distribution of znf76 transcripts was polarized to the anterior and posterior regions of the embryos, and znf76 transcripts were further restricted to the trigeminal placode and proctodeum posterior gut of the embryos at 18 h postfertilization (hpf). znf76 transcripts were localized to the midbrain–hindbrain boundary (MHB), hindbrain, and developing eyes at 24 hpf. Ectopic expression of znf76 with 5’-capped znf76 mRNA microinjected into embryos at the 1-cell stage caused phenotypic defects in the eyes, MHB, hindbrain, and spinal cord. Overexpression of znf76 resulted in a drastic reduction of pax2a, fgf8a, and rx1 transcripts in the optic stalk, MHB, and eyes, respectively. Taken together, these data indicate that Znf76 governs developmental processes in the MHB, hindbrain, and eyes in zebrafish embryos. We also discuss the Fgf8 signaling networks associated with the Znf76 function.